Life or death: disease-tolerant coral species activate autophagy following immune challenge - Fuess, Lauren E. (Proc Biol Sci, 2017)
Global climate change has increased the number and severity of stressors affecting species, yet not all species respond equally to these stressors. Organisms may employ cellular mechanisms such as apoptosis and autophagy in responding to stressful events. These two pathways are often mutually exclusive, dictating whether a cell adapts or dies. In order to examine differences in cellular response to stress, we compared the immune response of four coral species with a range of disease susceptibility. Using RNA-seq and novel pathway analysis, we were able to identify differences in response to immune stimulation between these species. Disease-susceptible species Orbicella faveolata activated pathways associated with apoptosis. By contrast, disease-tolerant species Porites porites and Porites astreoides activated autophagic pathways. Moderately susceptible species Pseudodiploria strigosa activated a mixture of these pathways. These findings were corroborated by apoptotic caspase protein assays, which indicated increased caspase activity following immune stimulation in susceptible species. Our results indicate that in response to immune stress, disease-tolerant species activate cellular adaptive mechanisms such as autophagy, while susceptible species turn on cell death pathways. Differences in these cellular maintenance pathways may therefore influence the organismal stress response. Further study of these pathways will increase understanding of differential stress response and species survival in the face of changing environments.